2023
DOI: 10.3389/fcvm.2023.1242608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of middle-term valve durability between transcatheter aortic valve implantation and surgical aortic valve replacement: an updated systematic review and meta-analysis of RCTs

Tsahi T. Lerman,
Amos Levi,
Troels Højsgaard Jørgensen
et al.

Abstract: BackgroundThis study aims to compare valve durability between transcatheter aortic valve implantation (TAVI) and surgical aortic valve replacement (SAVR).MethodsWe conducted a systematic review and meta-analysis using data from randomized controlled trials (RCTs). The primary outcome was structural valve deterioration (SVD). Secondary outcomes were bioprosthetic valve failure, reintervention, effective orifice area (EOA), mean pressure gradient, and moderate–severe aortic regurgitation (AR, transvalvular and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Compared with surgical aortic valves, evidence regarding the long-term durability of transcatheter aortic valves is limited. A recent meta-analysis of randomized controlled trials (RCTs) with follow-up periods of two to eight years found no significant difference in structural valve deterioration between SAVR and TAVR groups (10). However, the TAVR group had a significantly higher risk of reintervention [odds ratio (OR) 2.03; 95% confidence interval (CI): 1.34-3.05] and of moderate-severe aortic regurgitation (OR 6.54; 95% CI: 3.92-10.91) than the SAVR group (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with surgical aortic valves, evidence regarding the long-term durability of transcatheter aortic valves is limited. A recent meta-analysis of randomized controlled trials (RCTs) with follow-up periods of two to eight years found no significant difference in structural valve deterioration between SAVR and TAVR groups (10). However, the TAVR group had a significantly higher risk of reintervention [odds ratio (OR) 2.03; 95% confidence interval (CI): 1.34-3.05] and of moderate-severe aortic regurgitation (OR 6.54; 95% CI: 3.92-10.91) than the SAVR group (10).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of randomized controlled trials (RCTs) with follow-up periods of two to eight years found no significant difference in structural valve deterioration between SAVR and TAVR groups (10). However, the TAVR group had a significantly higher risk of reintervention [odds ratio (OR) 2.03; 95% confidence interval (CI): 1.34-3.05] and of moderate-severe aortic regurgitation (OR 6.54; 95% CI: 3.92-10.91) than the SAVR group (10). Regular long-term medical follow-up to evaluate the valve status is indicated for patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%